On the stability of invariant sets of a system of autonomous differential equations under constantly acting perturbations - Ignat'ev, A. O.; Konosevich, В. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We consider a system of ordinary autonomous differential equations that has an invariant set. We obtain sufficient conditions for the stability of this system under constantly acting perturbations.